Empowering Seaweed Farmers through the Anakonda Rote Method with Tissue Culture Seeds - Bessie, Donny; Umbu P. L. Dawa; Eka M. I. Seseli; Fredrik J. Haba Bunga; Jusuf Aboladaka; Susy Herawaty; Twenfosel O. Dami Dato; Nina Jeny Lapinangga (LP2M INSURI Ponorogo, 2025)
Holulai Village in Rote Ndao Regency is a coastal village with significant potential for seaweed cultivation. In 2024, the village produced 2,050 tons of dry seaweed, which serves as the economic backbone for many households. However, farmers face three major challenges: limited access to superior seedlings due to long-term reliance on aged cuttings, continued use of conventional off-bottom cultivation methods, and insufficient hygienic processing of seaweed-based products. To address these constraints, the Pemberdayaan Desa Binaan (PDB) program was implemented in collaboration with two farmer groups involving 40 active members. The program introduced the Anakonda Rote Net Method, combined with tissue–culture–derived seedlings, to enhance production performance and resilience. The results showed a substantial increase in seaweed biomass, with harvest weights rising from approximately 150–350 g per cultivation unit under conventional methods to 150–710 g using the Anakonda Rote Method, representing an increase of up to 100%. In addition, the program enabled farmers to diversify seaweed-based products into four hygienically processed variants (sticks, brownies, biscuits, and syrup), which increased product value and household income opportunities. Preliminary economic observations indicated reduced production losses due to pest attacks and improved post-harvest quality, which contributed to more stable incomes for participating households. Continuous mentoring and periodic monitoring are maintained to ensure the sustainability of seaweed cultivation and value-added processing in Holulai Village.